Memory Boxes. An Experimental Approach to Cultural Transfer in History, 1500-2000 (2014)
This volume discusses a practical approach to cultural transfer and exchange through the concept of »memory box«. Ideas of displacement, transfer, and cultural memory are explored through case studies from Scotland to Italy and Germany and from Finland and France to the American colonies. The authors develop an understanding of memory boxes as cultural constructions that are involved in the process of making and disputing memory – but which, simultaneously, are important agents for cultural transfer over space and time. This book emphasises »memory box« as an idea that allows us to study the cultural processes of transfer in conjunction with cultural memory.